Смарт-промисловість: визначення та теорія стимулювання розвитку на основі локального протекціонізму - Vyshnevskyi, Oleksandr S. (Institute of Industrial Economics of NAS of Ukraine, 2023)
The accelerated development of smart manufacturing is taking place all over the world, but the definition of the theoretical foundations of its stimulation, as well as the unequivocal understanding of "smart manufacturing" concept still has an untapped research potential. Therefore, the purpose of the article is to determine the theoretical foundations of stimulating the development of smart manufacturing in Ukraine based on local protectionism.The systematization and arrangement of concepts related to the Fourth Industrial Revolution (Industry 4.0) allows not only to clarify the concept of "smart manufacturing", but also to distinguish the concepts of "smart production", "smart maintenance", "smart manufacturing” and define the place of the latter in the system of interconnected concepts. Smart manufacturing is a part of smart production that concerns the production of tangible goods through the use of Industry 4.0 technologies embodied in smart services.Based on the definition and role of smart manufacturing, it becomes clear that smart manufacturing cannot exist without “ordinary” manufacturing, as well as conceptual directions for stimulating the development of smart manufacturing are distinguished, relating to: (1) sphere of smart services, generated by Industry 4.0 technologies; (2) sphere of smart production; (3) sphere of smart distribution; (4) sphere of smart exchange; (5) sphere of smart consumption; (6) sphere of production of smart products by smart manufacturing; (7) sphere of production of smart products by "ordinary" manufacturing; (8) sphere of production of "ordinary" products by smart manufacturing; (9) sphere of production of "ordinary" products by "ordinary" manufacturing.Given the reduction of national manufacturing in Ukraine, the development of services to ensure the smartization of manufacturing actually insures the smartization of foreign manufacturing that produces goods that are then imported into Ukraine. Therefore, it is advisable to stimulate the development of smart manufacturing in several directions at the same time: (1) stimulation of the manufacturing as a whole; (2) stimulating the development of smart services and tools for smartization of manufacturing; (3) stimulating the introduction of smart services in manufacturing; (4) stimulation of demand for products produced by the domestic smart manufacturing.There are two centers of smartization of manufacturing in Ukraine: (1) traditional manufacturing, as it invests in its own smartization; (2) a small business that creates smart services. The state, which in recent years has turned into an important player in the field of IT services, currently is not working purposefully on the smartization of manufacturing.In Ukraine there is also a contradiction between the need to harmonize the domestic economy with the EU market and the arrangement of favorable conditions for the development of smart manufacturing. This contradiction has the potential to be resolved on the basis of local protectionism theory through the expansion and improvement of the practice of applying special economic regimes (for instance, technology parks), and as well as the implementation of institutional and organizational solutions that simultaneously correspond to the provisions of both liberal and protectionist schools of economic theory.